ORGANIZATIONAL SKILL AND ITS RELATIONSHIP WITH THE MENTAL COMPOSURE OF ARABIC LANGUAGE TEACHERS IN THE ACADEMIC ACHIEVEMENT OF MIDDLE SCHOOL FEMALE STUDENTS IN THE SUBJECT OF ARABIC LANGUAGE (American Journal of Research in Humanities and Social Sciences, 2025)
The current study aims to identify the relationship between organizational excellence and mental resilience of Arabic language teachers in the academic achievement of Arabic language among middle school female students. The study community consists of all Arabic language teachers working in middle schools within the jurisdiction of the Directorate General of Education in Misan for the academic year 2023 - 2024, with a total of (36) middle schools in this directorate.The study sample was randomly selected from the middle schools affiliated with the General Directorate of Education in Misan, and the sample size consisted of (100) male and female teachers of Arabic language at the middle school level, distributed as follows: (50) male teachers and (50) female teachers. As for the students, they were chosen at a rate of (5) students for each teacher, making the total number of students (500). The researcher prepared her research tools: an organizational skill scale (20 items), an Arabic language achievement test (40 items), and a mental agility test (20 items), and the validity and reliability of each were established. The researcher used the Statistical Package for Social Sciences (SPSS22) to analyze the data collected after applying her research tools, and the results showed: The level of proficiency in the Arabic language curriculum is below the required standard, and their students' achievement is higher than the hypothetical average. The level of mental stability is below the minimum level that should be possessed by second-grade middle school students. The researcher has recommended a number of recommendations and proposals.